Rozważania teoretyczne dotyczące ewolucji zagranicznej polityki ekonomicznej Chińskiej Republiki Ludowej - Starzyk, Kazimierz (The Evolution of Foreign Policy of the People's Republic of China - Theoretical Considerations, 2008)
For the last three decades, the Chinese economy has experienced accelerated development, which led to its emergence as one of the top global players in the contemporary world economy. A crucial role in the development of the Chinese economy has been played along with internal factors by exogenous ones, including foreign trade, direct investment and the related technology transfer. This is reflected by an open development strategy implemented in this country, which is based on discounting benefits from international production specialization and export-oriented expansion. The foreign economic policy plays a fundamental role in the process. In general terms, the philosophy of the Chinese economic development was (and still is) oriented on continuous efficiency improvements reflected by a sharp increase in GDP, technical progress, internal and external equilibrium, improved competitiveness and increased welfare; ultimately the country is playing more and more important role in international industrial division of labour thanks to its foreign economic policy. The Chinese have gradually done so under the banner of "socialism with Chinese characteristics." In China, the emphasis has been upon the market transition over the political transition. Since the Chinese transition varies in objectives, means and factors, the measures as to success also differ. The experience of China can provide a valuable lesson for other transition economies in the field of foreign economic policy which is based upon sound theoretical economic assumptions. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 28, s. 237-249